Predictors of fistula formation after primary palatoplasty - Yarhere Kesiena Seun; Akadiri Oladimeji Adeniyi; Akinbami Babatunde Olayemi; Obiechina Ambrose Emeka (EDP Sciences, 2024)
Background: The goal of cleft palate repair is to create a seal between the oral and nasal cavities while improving speech by creating a functional velum. Various surgical techniques are at the surgeon's disposal to achieve this. Unfortunately, this sometimes fails, leading to formation of oronasal fistula. Objective: This study aimed to determine the predictors of oronasal fistula (ONF) formation following primary cleft palate repair. Methodology: This prospective interventional study involved cleft palate patients recruited from the University of Port Harcourt Teaching Hospital. Basic demographics and clinical data of participants were recorded preoperatively while morphometric measurements were taken under general anaesthesia to determine Cleft Palate Index and Cleft width. Four surgeons performed the procedures, and three surgical techniques were employed. Participants were followed up for a mean period of 5 months. The occurrence, location, and fate of ONF were documented. Correlation between ONF and potential predictor variables was tested, and determinant(s) of fistula formation was explored. Data was analysed using IBM SPSS version 21.0 with statistical significance set at P < 0.05. Result: Eighty-two participants with ages ranging from 9 months to 19 years completed the study. The initial incidence of ONF was 29.3% but 16.7% of these cases resolved spontaneously within 5 weeks. Cleft Palate Index, Cleft width, and time (age) of repair significantly correlated with occurrence of ONF. However, Cleft width was the only statistically significant (p = 0.049) individual determinant of fistula formation. Conclusion: In this study, Cleft width W is the most important predictor of ONF formation.